Xanthogranulomatous Orchitis Presenting as a Scrotal Mass in an Elderly Male: Malignancy or Mimicker?. Issue 12 (December 2019) - Sharma, Pooja; Ramteke, Prashant; Satapathy, Abhishek; Ray, MD
Xanthogranulomatous inflammation is a rare, destructive pattern of inflammation, affecting different organs, that often produces a mass-like lesion, simulating malignancy. Although benign, it can coexist with malignancy. We, herein, report the case of a 60-year-old male patient, who presented with a testicular mass that was partly necrotic and showed heterogeneous enhancement on contrast study. Testicular tumor markers were normal. In view of clinicoradiological suspicion of a malignant cause, high inguinal orchidectomy was performed. However, histopathology showed features of a xanthogranulomatous orchitis with no evidence of any malignancy. Pathologists must be aware of this entity as definitive diagnosis requires histopathologic examination and adequate sampling must be done to rule out a coexistent malignancy.